Is Ramsar Home Yet? A Critique of South Korean Laws in Light of the Continuing Coastal Wetlands Reclamation - Kim, Rakhyun E. (Columbia Journal of Asian Law, 2011)
One of the ways the clash between economic development and environmental protection in South Korea is manifested is in the country’s policies on coastal land use and reclamation. Even though coastal wetlands are legally considered public property, they have been continuously reclaimed and privatized by the state and its close corporate entities under the Public Waters Reclamation Act of 1962. Since its accession to the Ramsar Convention (the “Convention”), Korea has been curtailing the privatization of public lands. The country has instituted domestic measures to implement the provisions of the Convention and to follow the principle of sustainable use of wetlands. Coastal law and policy have also gained political prominence since Korea hosted the Tenth Ramsar Conference in 20o8. Efforts to uphold the country’s obligations under the Convention and to limit large-scale coastal reclamation projects, however, have not been effective. Over 1,ooo square kilometers of coastal wetlands, or thirty percent of the remaining wetlands, are currently being developed. In addition, numerous special development laws, providing loopholes for developers to circumvent limits on land reclamation projects,. have been passed. This article reviews South Korea’s legal and institutional landscape and examines the question of whether the Ramsar Convention has been genuinely internalized by the legal system. Domestic laws are insufficient in upholding the principles of the Convention, and government administrators are not committed to upholding them. This article ultimately concludes that Korean law needs to adopt and internalize certain outside norms in order to effectively carry out Korea’s obligations under the Ramsar Convention.